Addressing racism in the workplace through simulation: So much to unlearn - Fricke, Moni; Beach Ducharme, Debra; Beavis, Allana; Flett, Priscilla; Oosman, Sarah (Frontiers in Rehabilitation Sciences, 2023)
Introduction Racism exists in the healthcare system and is a root cause of health inequities among Indigenous Peoples. When microaggressions of racism are carried out by healthcare providers, therapeutic trust may be broken and quality of care may be impacted. Anti-racism response training is considered best practice in recognizing and addressing racism. A 90-minute virtual anti-racism simulation workshop for rehabilitation therapists was developed and delivered virtually four times across Canada between 2020 and 2021. Following an introduction and pre-briefing, role-playing among participants was used to address microaggressive Indigenous-specific racism, followed by an in-depth debriefing with trained facilitators. A post-workshop survey was conducted to assess the impact of this anti-racism simulation workshop among occupational therapists (OTs) and physiotherapists (PTs). Methods Following each simulation workshop, participants were invited to complete an anonymous post-activity survey (n= 20; 50% OTs, 45% PTs). Open text responses were analyzed thematically from the perspective of critical race theory. Results The majority of the participants self-identified as women (95%); white (90%); mid-career (52%); and had never personally experienced racism (70%). All participants agreed that the workshop gave them ideas on how to start dismantling racism in their workplace. Thematic analysis resulted in four themes: so much to unlearn, remain humble, resist the silence, and discomfort is okay. Discussion There is a growing number of rehabilitation therapists ready to be engaged in anti-racism conversations while addressing the truths of colonization and striving for reconciliation. Virtual anti-racism training provides a viable and effective means of leaning into these brave conversations.